The Effectiveness of International Efforts to Suppress the Crime of Genocide - Al-Alwani, Khalid (Journal of Legal Sciences, 2026)
It can be said that the crime of genocide, and the conduct it entails, constitutes a profound affront to the conscience of humanity, as it targets not only the individual as a human being but also their very humanity. This crime is driven by the highest forms of racial discrimination, aiming at the annihilation of a specific group of people for no other reason than their belonging to that group. The intention to eliminate such a group arises from a deeply rooted malice, forming a special intent that leads perpetrators to commit the crime through systematic conduct and deliberate planning. Genocide often occurs in the context of armed conflict, which adds a grave dimension to its impact, as it threatens the unity of society and its inherent diversity.The atrocities committed during many armed conflicts, which have claimed the lives of hundreds of thousands of individuals solely due to their group affiliation, have exposed the horrific nature of this crime. The world stood in shock in the face of such atrocities, prompting the international community to intensify efforts to combat, prevent, and suppress genocide. These efforts have taken the form of developing international legal instruments that define the crime and its material elements, as well as judicial mechanisms aimed at prosecuting perpetrators, ensuring accountability, delivering individual deterrence, and upholding the requirements of general deterrence to prevent recurrence.Despite the importance of these international efforts, they have not succeeded in fully achieving their objectives. Numerous conflicts that have taken place in the aftermath continue to witness horrific manifestations of genocide. This research addresses a central problem expressed through the following question: To what extent have international efforts succeeded in confronting the crime of genocide and addressing its surrounding challenges? And how effective have these efforts been in suppressing this crime?